Pure trapezio-metacarpal dislocation - a rare injury - Khan, Abdul Qayyum; Khan, Gul Ar Navi; Khan, Zafar Ahmad (International Journal of Research in Medical Sciences, 2016)
Isolated trapezio-metacarpal dislocation is a rare condition, generally occurs due to fall on outstretched hand. These injuries are sometimes missed in polytrauma patients or sometimes neglected as in underdeveloped world. Various treatment modalities are used, including conservative and surgical options; however no gold standard approach exists for this rare injury. This case report aims to report outcome of a trapezio-metacarpal (TM) dislocation of a patient who was treated conservatively with excellent functional outcome.